Local Food Diversification Development Strategy in West Sumbawa Regency - Eko Supriastuti; Anton Anton; Ari Apriani; Fikri Rirahman (Jurnal Biologi Tropis, 2023)
A method of food selection known as "food diversification" does not rely solely on one type of food but rather on a variety of food ingredients, starting with production, processing, distribution, and household food consumption. West Sumbawa Regency is a potential area in the development of alternative local food crops to replace rice, such as yam, corn and other tubers. This study aims 1) To determine the factors that influence local food diversification in West Sumbawa Regency 2). Formulate a strategy for developing local food diversification in West Sumbawa Regency. This study employs SWOT analysis in a descriptive manner. Results using the SWOT analysis obtained five strategies, of the five existing strategies three strategies were obtained which were prioritized, namely: 1). maximizing the utilization of land potential and local food consumption habits to support the success of food diversification, 2). Increasing human resources in producing local food variations and increasing the habit of consuming local food in anticipation of the mushrooming of restaurants with modern/imported food, 3). Creating new markets through agro-industry, in the provision of diverse and quality food so as to increase income. The conclusion is that the food diversification strategy was based on internal and external factors by analyzing opportunities, threats, strengths, and weaknesses and generating three prioritized strategies.